The role of antioxidants in facial nerve injury - Lee, Jae Min; Byun, Seong Wook; Kim, Sung Soo; Park, Kyung Sun; Ryoo, Jae-Hong; Yeo, Seung Geun (Frontiers in Molecular Biosciences, 2025)
Oxidative stress contributes to the pathogenesis of facial nerve injury (FNI), yet the role of antioxidants in driving regeneration and functional recovery remains incompletely defined. This narrative review synthesizes studies published between 2008 and 2025 that evaluated antioxidant interventions in FNI across animal and limited human contexts. We systematically searched five databases and included 19 studies assessing oxidative stress markers and neural outcomes following antioxidant administration. To avoid overgeneralization, we stratified findings by injury model—crush/compression, transection with anastomosis, and ischemic/viral—and by primary endpoints (electrophysiology/behavior vs. histology/biochemistry), and, where reported, by intervention timing and dose. Antioxidants commonly reduced reactive oxygen species and modulated survival and inflammatory pathways, supporting neuroprotection and, in some models, improved electrophysiological or behavioral readouts. However, benefits varied by model and regimen: crush injuries showed earlier functional gains, whereas transection models more often demonstrated histological improvement without consistent short-term functional recovery; ischemic/viral studies frequently lacked standardized electrophysiological confirmation. Outcomes were also contingent on timing and dose (with earlier initiation and moderate dosing generally more favorable), and select combinations showed additive effects in preclinical settings. Overall, the evidence is predominantly preclinical, heterogeneous in dosing/timing/formulations, and limited by small sample sizes and inconsistent functional outcomes. Antioxidant strategies should therefore be considered hypothesis-generating rather than clinically recommendable at this time. Future research should use model-appropriate, standardized functional endpoints, prespecify timing/dose exploration, evaluate rational combinations, and conduct well-powered clinical trials to establish efficacy, optimal use, and safety.